2021
DOI: 10.1109/toh.2020.2996748
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Wearable Haptics and Obstacle Avoidance for the Visually Impaired in Indoor Navigation: A User-Centered Approach

Abstract: Recently, in the attempt to increase blind people autonomy and improve their quality of life, a lot of effort has been devoted to develop technological travel aids. These systems can surrogate spatial information about the environment and deliver it to end-users through sensory substitution (auditory, haptic). However, despite the promising research outcomes, these solutions have met scarce acceptance in real-world. Often, this is also due to the limited involvement of real end users in the conceptual and desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 35 publications
2
32
0
2
Order By: Relevance
“…User interface and feedback modalities are essential features to take into consideration during system development because they have the ability to enhance the accessibility and usability of a system application [85]. This review demonstrated that audio was a common choice for feedback information to the user, which corroborates the results found in Islam et al [82] and Kuriakose et al [83].…”
Section: B Feedbackssupporting
confidence: 83%
See 1 more Smart Citation
“…User interface and feedback modalities are essential features to take into consideration during system development because they have the ability to enhance the accessibility and usability of a system application [85]. This review demonstrated that audio was a common choice for feedback information to the user, which corroborates the results found in Islam et al [82] and Kuriakose et al [83].…”
Section: B Feedbackssupporting
confidence: 83%
“…In accordance with our findings, several studies have reported that to develop successful and satisfactory assistive technologies, the development must follow human-centered design approach [88]. Therefore, it is essential to understand how visually impaired people move in unknown environments and what are their needs and requirements [84], [85], [89]. In agreement, Kuriakose et al [83] argue that most solutions that may work in theory are not adopted in practice because they do not meet the user's requirements.…”
Section: User Evaluationsupporting
confidence: 82%
“…Navigation aids with smartphones as the core account for more than one-third of the total, and the classifications of 'with Infrastructure' and 'Alone' are similar. Computer-based systems mainly use external vision sensors to collect the required data [56,64] and rarely use pre-set infrastructure. Due to the enhancement of the computing power, portability, durability, and affordability of smartphones, systems with smartphones as the core have engendered a trend to replace these tasks with computers.…”
Section: Hardware Compositionmentioning
confidence: 99%
“…Falcon haptic also integrated with a laser sensor to applied in a wheelchair with the purpose is support blind people [10], and the nuclear industry [11]. For some applications used the haptic to make feedback force to the user to help avoid obstacles is as in [12], [13]. In the UAV field, the end-effector of Falcon haptic is used to set velocity command for the UAV [14], [15], and the force feedback to haptic is to help the user avoiding obstacles that closed the UAV [16]- [18].…”
Section: Introductionmentioning
confidence: 99%